Security analyst superiority relative to univariate time-series models in forecasting quarterly earnings - Brown, Lawrence D.; Hagerman, Robert L.; Griffin, Paul A.; Zmijewski, Mark E. (Journal of Accounting and Economics, 1987)
This paper provides evidence of security analyst (SA) superiority relative to univariate time-series (TS) models in predicting firms' quarterly earnings numbers and shows that SA forecast superiority in our sample is attributable to: (1) better utilization of information existing on the date that TS model forecasts can be initiated, a contemporaneous advantage; and (2) use of information acquired between the date of initiation of TS model forecasts and the date when SA forecasts are published, a timing advantage.